2014
DOI: 10.3892/or.2014.3198
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel HLA-A*02:01-restricted cytotoxic T lymphocyte epitope derived from the EML4-ALK fusion gene

Abstract: Cancer immunotherapy is a promising new approach to cancer treatment. It has been demonstrated that a high number of tumor-specific cytotoxic T cells (CTLs) is associated with increased disease-specific survival in lung cancer patients. Identification of superior CTL epitopes from tumor antigens is essential for the development of immunotherapy for malignant tumors. The EML4-ALK fusion gene was recently identified in a subset of non-small cell lung cancers (NSCLCs). In this study we searched for HLA-A*02:01- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…To evaluate the immunogenic potential of the five predicted HLA-A * 02:01-binding peptides derived from EGFR T790M, we attempted to induce peptide-specific CTLs from human PBMCs obtained from four healthy donors. Several reports have shown the usefulness of artificial antigen-presenting cells (aAPCs) for the induction and expansion of peptide-specific CTLs from PBMCs ( 23 , 24 ). Thus, we attempted to induce such CTLs using aAPCs.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the immunogenic potential of the five predicted HLA-A * 02:01-binding peptides derived from EGFR T790M, we attempted to induce peptide-specific CTLs from human PBMCs obtained from four healthy donors. Several reports have shown the usefulness of artificial antigen-presenting cells (aAPCs) for the induction and expansion of peptide-specific CTLs from PBMCs ( 23 , 24 ). Thus, we attempted to induce such CTLs using aAPCs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that peptides derived from chimeric ALK protein could generate anti-ALK-specific CD8 C T cells. 36 These cells have also been detected in cancer patients with ALK rearrangements. 26,27 We did not investigate the presence of anti-ALK-specific T cells in our series of ALK-positive ADC, but indirect arguments suggest that antitumor CD8 C T cells were present.…”
Section: Discussionmentioning
confidence: 84%
“…A substantial number of HLA-A*02:01-restricted cytotoxic T lymphocyte epitopes closely related to tumors have been identified so far [8]. In order to illustrate the performance of HLABAP, the experimentally determined pIC50 values and the predicted binding affinities of the peptides against HLA-A*02:01 were compared in this study.…”
Section: Methodsmentioning
confidence: 99%